Comparison of Prophylactic Options for Post-Operative Endophthalmitis after Cataract Extraction with Intra Ocular Lens Implantation - Bilal Humayun Mirza, Ali Raza, Kashif Siddique (Journal of Rawalpindi Medical College, 2013)
Background: To compare prophylactic use of intracameral Moxifloxacin (Vigamox) with subconjuctival injection of Ceftriaxone and Dexamethasone in prevention of post operative endophthalmitis after cataract extraction with intra ocular lens implantation Methods: In this comparative study patients with uncomplicated cataracts were selected and divided into two groups. Each patient of group 1 was given an intracameral injection of 500μg/0.1ml moxifloxacin (vigamox) and each patient of group 2 was given subconjunctival injection of ceftriaxone and dexamethasone as a last step of the cataract extraction surgery with IOL implantation. Result: No significant reaction was seen in the anterior chamber of the patients during the 6 week post operative follow up in 357 patients. One patient had significant post operative anterior chamber flare and cells without the formation of hypopion. Conclusion: Moxifloxacin is effective in preventing the post operative endophthalmitis after cataract extraction surgery with IOL implantation.